Use of variables for implementing compensatory techniques in urbanized areas: Case study in Araraquara - SP - Lopes, Bruna Lamorea Veiga; Teixeira, Bernardo Arantes do Nascimento (National Journal of City Management, 2025)
Objective - To demonstrate the use of pre-selected variables to optimize the selection of compensatory techniques (CT) for implementation with greater accuracy in already urbanized areas, through a case study in Araraquara-SP, Brazil.Methodology - The study employed an applied and empirical approach based on bibliographic review and field analysis. The selected area was the micro-basin of the Servidão Stream, located in the central region of Araraquara-SP, where flooding occurs frequently. Specific variables were defined and applied to assess the feasibility of implementing different CTs in urbanized areas, allowing for the selection of solutions most appropriate to the local context.Results - The analysis revealed that factors such as the unavailability of space, feasibility of implementation in public and private areas, interference of construction works with existing activities, and the possibility of dispersing runoff discharges to different receiving bodies are crucial considerations when selecting the most appropriate CT.Originality/Relevance - This study addresses both theoretical and practical gaps regarding the challenges of implementing CTs in already consolidated urban areas. It contributes by proposing a novel set of variables that guide the selection of sustainable urban drainage techniques, considering typical limitations of densely occupied urban spaces. Its relevance lies in the practical applicability for municipalities facing chronic flooding problems.Theoretical/Methodological Contributions - The study proposes a matrix of variables for evaluating the feasibility of implementing CTs in consolidated urban areas, representing a methodological advancement. The systematization of these variables enables a more rigorous and standardized analysis in the selection of technical solutions, contributing to the literature on sustainable urban drainage and integrated urban planning.Social and Environmental Contributions - CTs provide benefits such as flood reduction, improvement of urban environmental quality, and enhancement of public spaces. Their implementation can significantly improve urban mobility, population quality of life, and preservation of water bodies, provided there is community participation and institutional support. Public awareness and social acceptance are emphasized as key factors for the success of such interventions.
Keywords: Urban Drainage; Compensatory Techniques; Rainwater